Dynamic and operational capabilities for innovation: their influence on export market effectiveness - Vicente, Margarida (2017)
This paper analyzes the influence of technological turbulence, organizational management dynamic capability and operational capabilities for innovation on export market effectiveness. Based on the dynamic capability view, we investigate the effect of technological turbulence on organizational management dynamic capability, and how this latter contributes to leverage operational capabilities for innovation in order to benefit performance in export markets. To test the hypotheses, we carry out a structural equation model, using a sample of 471 exporting manufacturers firms that operate from Portugal. The results demonstrate that technological turbulence is an antecedent factor of organizational management dynamic capability, which in turn has a significant impact on the development of firms’ operational capabilities for innovation, specifically innovativeness, innovation strategy, and technological capability. However, the findings only establish that innovation strategy and technological capability have a significant direct effect on export market effectiveness. Implications for scholars and practitioners are discussed along with suggestions for future research.